Audio Description from a discourse perspective: a socially relevant framework for research and training - Braun, Sabine (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The topic of this paper is Audio Description (AD) for blind and partially sighted people. I will outline a discourse-based approach to AD focussing on the role of mental modelling, local and global coherence, and different types of inferences (explicatures and implicatures). Applying these concepts to AD, I will discuss initial insights and outline questions for empirical research. My main aim is to show that a discourse-based approach to AD can provide an informed framework for research, training and practice.